Liquid film–induced critical heat flux enhancement on structured surfaces - Li, Jiaqi (Sci Adv, 2021)
Enhancing critical heat flux (CHF) during boiling with structured surfaces has received much attention because of its important implications for two-phase flow. The role of surface structures on bubble evolution and CHF enhancement remains unclear because of the lack of direct visualization of the liquid- and solid-vapor interfaces. Here, we use high-magnification in-liquid endoscopy to directly probe bubble behavior during boiling. We report the previously unidentified coexistence of two distinct three-phase contact lines underneath growing bubbles on structured surfaces, resulting in retention of a thin liquid film within the structures between the two contact lines due to their disparate advancing velocities. This finding sheds light on a previously unidentified mechanism governing bubble evolution on structured surfaces, which has notable implications for a variety of real systems using bubble formation, such as thermal management, microfluidics, and electrochemical reactors.